Towards the New World Order: Theoretical Interpretations and Practical Implementations - K. A. Efremova (Сравнительная политика)
The problem of political and economic regulation of contemporary global transformations, taken in the context of the New World Order discourse, attracts attention in Russia and abroad alike. Considering this problem, British analysts Ken Booth and Nickolas Wheeler underline three major approaches to security dilemma, namely, fatalist, mitigator, and transcender logics. Followers of the fatalist approach (neo-realists, globalists) believe that world order is a zero-sum game, where interstate interactions are mostly confrontational, and their pattern depends on the current balance of power. Mitigators (neo-liberals, functionalists, constructivists, etc.) insist that the emerging world order is a win-win game, where nations opt for investing some of their sovereignty into newly created international institutions (regimes and organizations), hoping that conventional rules adopted by them would help to decrease international uncertainty, which otherwise might lead to confrontation. Transcenders (neo-Marxists, feminists, anarchists, federalists, etc.) consider the existing world order an archaic one, calling for a new, fair and humane pattern of international relations. According to their logic, the new world order is the end of the game among sovereign states, because it derives from the idea of humankind not divided by national boundaries but united into a global transnational society.